Exiting war the British empire and the 1918-20 moment - Fathi, Romain 1987-; Hutchison, Margaret; Varnava, Andrekos 1979-; Walsh, John K. 1939-1990 (Manchester University Press, 2022)
Exiting war explores a particular 1918-20 'moment' in the British Empire's history, between the First World War's armistices of 1918, and the peace treaties of 1919 and 1920. That moment, we argue, was a challenging and transformative time for the Empire. While British authorities successfully answered some of the post-war tests they faced, such as demobilisation, repatriation, and fighting the widespread effects of the Spanish flu, the racial, social, political and economic hallmarks of their imperialism set the scene for a wide range of expressions of loyalties and disloyalties, and anticolonial movements. The book documents and conceptualises this 1918-20 'moment' and its characteristics as a crucial three-year period of transformation for and within the Empire, examining these years for the significant shifts in the imperial relationship that occurred and as laying the foundation for later change in the imperial system
Keywords: Geschichte 1918-1920; Imperialismus; Kolonie; Großbritannien; World War, 1914-1918 / Great Britain / Influence; Great Britain / Colonies / History / 20th century; Commonwealth countries / History / 20th century; Great Britain / History / George V, 1910-1936; British colonies; Influence (Literary, artistic, etc.); Commonwealth countries; Great Britain; 1900-1999; History; Aufsatzsammlung